Epithelial endoplasmic reticulum stress orchestrates a protective IgA response - Grootjans, Joep; Krupka, Niklas; Hosomi, Shuhei; Matute, Juan D.; Hanley, Thomas; Saveljeva, Svetlana; Gensollen, Thomas; Heijmans, Jarom; Li, Hai; Limenitakis, Julien P.; Ganal-Vonarburg, Stephanie C.; Suo, Shengbao; et al. (Science (American Association for the Advancement of Science), 2019)
Immunoglobulin A (IgA) is the major secretory immunoglobulin isotype found at mucosal surfaces, where it regulates microbial commensalism and excludes luminal factors from contacting intestinal epithelial cells (IECs). IgA is induced by both T cell–dependent and –independent (TI) pathways. However, little is known about TI regulation. We report that IEC endoplasmic reticulum (ER) stress induces a polyreactive IgA response, which is protective against enteric inflammation. IEC ER stress causes TI and microbiota-independent expansion and activation of peritoneal B1b cells, which culminates in increased lamina propria and luminal IgA. Increased numbers of IgA-producing plasma cells were observed in healthy humans with defective autophagy, who are known to exhibit IEC ER stress. Upon ER stress, IECs communicate signals to the peritoneum that induce a barrier-protective TI IgA response.